Особливості регулювання рівня напруги, що стабілізується, за допомогою перетворювача з трансформаторно-ключовою виконавчою структурою - Липківський, К.О. (Технічна електродинаміка, 2012)
The problem of voltage changer design that will maintain two types of transformation simultaneously (purposeful change of the voltage level and its stabilization at this level) is reasonable to solve by means of transformer-andswitches executive structures. The overall (idealized) and practically reachable Input-Output characteristics of such changers are examined in the research paper. It was proved that in spite of discretely-one manner, a smooth setpoint of stabilized voltage level is possible. It was shown that in case of need the stabilization at each level may happen over its range that is much wider than normalized range for all the levels in whole